Does previous arthroscopic Bankart repair influence coracoid graft osteolysis in Latarjet procedure? A case-control study with computed tomography scan data - Şahin, Koray; Sarıkaş, Murat; Çeşme, Dilek Hacer; Topal, Murat; Kapıcıoğlu, Mehmet; Bilsel, Kerem (Elsevier BV, 2024)
The Latarjet procedure is commonly performed in the treatment of recurrent shoulder instability and is also indicated as a salvage procedure for recurrence after failed arthroscopic Bankart repair. Although this procedure has shown success, there has been an increased awareness of complications in recent studies, especially graft osteolysis. Most relevant research has focused on the pathophysiology, incidence, or location of graft osteolysis or the risk factors for graft osteolysis; however, the data are limited to primary Latarjet procedures. This study aimed to investigate the effect of previous arthroscopic Bankart repair surgery on coracoid bone graft osteolysis in the Latarjet procedure.This retrospective case-control study analyzed data from patients who underwent primary Latarjet procedures or revision Latarjet procedures following failed arthroscopic Bankart repair. Clinical outcome measures included range of motion, the Subjective Shoulder Value, and the Rowe score. Volumetric analysis of each transferred coracoid graft was performed using early postoperative and late postoperative computed tomography scan data, and the amount of graft osteolysis was then calculated as the percentage of volume reduction of each graft.A total of 32 patients who met the inclusion criteria were included in this study, with 24 patients in the primary Latarjet group (group I) and 8 patients in the revision Latarjet group (group II). The mean age of the patients was 32.5 ± 7.7 years, and the mean follow-up duration was 52.1 ± 8.9 months. Both study groups showed significant improvement in the Subjective Shoulder Value compared with baseline (P < .05). Comparison of postoperative clinical outcome measures showed no significant difference in any outcome parameter between the 2 study groups (P > .05). No recurrence was observed during the follow-up period. A positive apprehension sign was present in 6 patients (25%) in group I and 4 patients (50%) in group II (P > .05). Analysis of radiologic data revealed that all patients underwent some degree of graft osteolysis, with varying osteolysis ratios between 12% and 98%. The mean osteolysis ratio of the coracoid graft was 67.3% ± 22.6% in group I and 69.4% ± 25.6% in group II, with no significant difference between the 2 groups (P > .05).The findings of this study suggest that a considerable amount of coracoid graft osteolysis is observed after both primary Latarjet procedures and revision Latarjet procedures following failed arthroscopic Bankart repair. Previous arthroscopic Bankart repair did not seem to have a significant influence on the amount of graft osteolysis, and both primary and revision Latarjet procedures showed satisfactory clinical outcomes.
Keywords: Adult; Joint Instability; Young Adult; Arthroscopy; Shoulder Joint; Recurrence; Shoulder Dislocation; Case-Control Studies; Humans; Osteolysis; Tomography, X-Ray Computed; Retrospective Studies